Sistem Informasi Manajemen Apotek Menggunakan Metode Extreme Programming - Putri Saraswati; Zaid Amin (Journal of Information System Research (JOSH), 2023)
Prima Angel's Pharmacy is engaged in the health sector and is located on Jl. Ki Merogan No. 117, Kertapati Palembang. Prima Angel's Pharmacy is a pharmacy that buys and sells medicines needed by the community. The current system at Prima Angel's pharmacy is still using the conventional system which is manually doing the record of purchase and sale transactions into a ledger, thus making the data processing, data search, and report generation become inefficient. The purpose of this research is to facilitate data processing and data storage, so that the data can be neatly arranged and easily processed into the required information. This Prima Angel's Pharmacy management information system was built with a combination of research methods between qualitative methods in terms of system development using Extreme Programming and quantitative methods using descriptive statistical data analysis. The results of the development of the Prima Angel's Pharmacy management information system can run as expected, namely processing data, searching data, and making reports effectively and efficiently.